2021
DOI: 10.1111/flan.12600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the reading and listening outcomes of beginning‐level Duolingo courses

Abstract: The Challenge As more and more learners use digital apps to learn languages, it is important for the field of language learning to understand the effectiveness of these apps. This article presents the listening and reading proficiency of Duolingo learners when they reach the end of its beginning-level Spanish and French courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…It has been researched around the globe, including places such as Taiwan (Charlene Tsai 2016), 3 my native Poland (Uchwat-Zaród 2020; Krajka & Białek 2021, or Aleksandrowska & Stanulewicz 2020 and many other European countries, including Eastern Europe (Federova 2018;Kvitka 2020) and Greece (Karasimis 2020). The current research has been informed also by research from Iran (Nushi & Eqbali 2017), Israel (Gafni et al 2017), from the Arabic linguistic context (Ahmed 2016), from Borneo (Ajisoko 2020), as well as from the Americas, including Columbia (Abaunza et al 2019) and, of course, the U.S. (Short et al 2021;Jiang et al 2021). Some of the studies involve international samples, like Tafazoli et al (2018) or Cebron et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been researched around the globe, including places such as Taiwan (Charlene Tsai 2016), 3 my native Poland (Uchwat-Zaród 2020; Krajka & Białek 2021, or Aleksandrowska & Stanulewicz 2020 and many other European countries, including Eastern Europe (Federova 2018;Kvitka 2020) and Greece (Karasimis 2020). The current research has been informed also by research from Iran (Nushi & Eqbali 2017), Israel (Gafni et al 2017), from the Arabic linguistic context (Ahmed 2016), from Borneo (Ajisoko 2020), as well as from the Americas, including Columbia (Abaunza et al 2019) and, of course, the U.S. (Short et al 2021;Jiang et al 2021). Some of the studies involve international samples, like Tafazoli et al (2018) or Cebron et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the studies involve international samples, like Tafazoli et al (2018) or Cebron et al (2021). There is an abundant body of research on Duolingo-enhanced learning of English (see Short et al 2021, for more detailed information; de Castro et al 2016;Tafazoli et al 2018) and other popular languages like Spanish or French (Jiang et al 2021). Some studies include learning two or more languages (Ahmed 2016;Charlene Tsai 2016), up to fifteen, as the one conducted by Aleksandrowska and Stanulewicz (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The students in the second, more advanced group, found the app helpful (80%), but only 43.8% of the students enjoyed using it, and only 50% of the class was actually satisfied with Duolingo (strongly agree and agree). Jiang et al (2020) report their results of a study on 225 participants, who were students of Spanish or French and resided in the United States, had little to no prior proficiency in the target language and used Duolingo as their only learning tool. The results showed that the students reached Intermediate level in reading proficiency but remained at Novice level in listening proficiency (assessed using the American Council on the Teaching of Foreign Languages (ACTFL) reading and listening proficiency tests).…”
Section: Introductionmentioning
confidence: 99%